2014
DOI: 10.1007/s00405-014-3261-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of selected risk factors for nodal metastases in head and neck cutaneous squamous cell carcinoma

Abstract: Cutaneous squamous cell carcinoma (cSCC) accounts for 20 % of all skin malignancies and 20 % of deaths. In contrast to mucosal SCC, treatment results are very good. However, regional metastases are present in 5–20 % of cases, and the prognosis for patients with metastases is 50 % lower. It has been reported that several risk factors are responsible for the head and neck lymph node regional metastasis, such as: poor cell differentiation, local recurrence, immunosuppression, and tumour dimension. Multivariate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 25 publications
3
23
0
Order By: Relevance
“…According to Cox regression, however, histopathological grading ( ≥ G3) only tends to be an independent prognostic parameter for metastasis ( p = 0.058, Table 2 ). Recent analyses displayed a metastatic risk of G3 tumours between 17.9 and >30% [24,32,34,37,39,40] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Cox regression, however, histopathological grading ( ≥ G3) only tends to be an independent prognostic parameter for metastasis ( p = 0.058, Table 2 ). Recent analyses displayed a metastatic risk of G3 tumours between 17.9 and >30% [24,32,34,37,39,40] .…”
Section: Discussionmentioning
confidence: 99%
“…Table 1). Poor differentiation is correlated with an increased metastatic risk and part of the ''high-risk-features'' in the AJCC classification of cSCC [8,12,24,32,34,[36][37][38] . The univariate analysis revealed that ≥ G3 tumours are significantly associated with metastasis ( p = 0.036).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike tumors on the trunk and extremities, cutaneous SCCs of the head and neck present with a higher incidence of lymph node metastasis . Certain characteristics portend a higher risk: primary tumor >2 cm, tumor thickness >4–5 mm, tumor location near the parotid gland (ear, temple, forehead, and anterior scalp), recurrent tumors, poorly differentiated or desmoplastic tumors, lymphovascular or perineural invasion and an immunocompromised host …”
Section: Head and Neck Cutaneous Squamous Cell Carcinomamentioning
confidence: 99%
“…Cutaneous squamous cell carcinoma (cutaneous SCC) is the second most common skin cancer in the United States and accounts for 20% of all non‐melanoma skin cancer . While the majority of cutaneous SCC cases have a favorable prognosis, a subset displays a more aggressive clinical trajectory including increased rates of local recurrence, lymph node metastasis and death . A standard of care has not been defined for management of these patients and no prognostic algorithms exist to predict which individuals are at risk for local recurrence or metastasis .…”
mentioning
confidence: 99%
See 1 more Smart Citation